Diagnosis And Management Of Stroke-Associated Pneumonia: A Mixed-Methods Study - Zawiah, Mohammed Hussein Ali Hussein (2023)
Stroke-associated pneumonia (SAP) is a complication that commonly occurs within the first week of an acute stroke and is associated with prolonged hospitalization and increased mortality. Diagnosing and treating SAP is challenging due to the lack of gold-standard criteria. Researchers have investigated both antibiotics and non-antibiotic preventive medications for SAP. However, antibiotics have been found to be ineffective in preventing SAP, and the effectiveness of non-antibiotic drugs is still controversial. Additionally, predictive biomarkers have also been studied, but their performance has been inconsistent.